Property Impacts on Plate-fin Multi-stream Heat Exchanger (Cold Box) Design in CO2 Cryogenic Process: Part II. Evaluation of Viscosity and Thermal Conductivity Models. (May 2017) - Tan, Yuting; Nookuea, Worrada; Li, Hailong; Thorin, Eva; Yan, Jinyue
Abstract: Viscosity and thermal conductivity are key transport properties in the design of plate-fin multi-stream heat exchanger in CO2 cryogenic processes. It is necessary to evaluate the reliabilities of viscosity and thermal conductivity models. In addition, the differences in design of multi-stream heat exchanger by using different property models need to be studied as well. In this paper, viscosity models and thermal conductivity models of CO2 mixtures with non-condensable gas impurities were evaluated separately by comparison with existing experimental data. Recommendations were given on model selections and their impact on the design of plate-fin multi-stream heat exchanger were analyzed. The results show that for viscosity, the uncertainty range of Wilke's model is the smallest with a maximum absolute deviation of 6.1%. This model is therefore recommended to be used. For thermal conductivity, GERG model, with a maximum absolute deviation of 8.7% is preferred. The choice of thermal conductivity model has a noticeable impact on the plate-fin multi-stream heat exchanger design, and the maximum deviation by using different thermal conductivity models is 7.5%.